PERANAN GURU DALAM MENGEMBANGKAN KEPERCAYAAN DIRI ANAK USIA 4-5 TAHUN DI TK MAZMUR 21 PONTIANAK SELATAN - Natalia, Silvi Efriska; Fadillah, Fadillah; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstrackSelf-confidence is a personality trait that implies confidence in one's own abilities. Children Â self confidence is very influenced by how parents or educators grow their self confidence. A common issue in this study is